KAJIAN TERHADAP KESEDARAN DAN KESEDIAAN PELAJAR JABATAN KEJURUTERAAN ELEKTRIK DALAM PENGGUNAAN CIDOS DI POLITEKNIK SULTAN SALAHUDDIN ABDUL AZIZ SHAH - Saim, Aishah Binti; Talib, Saharuddin Bin; Zakaria, Roshidi Bin (Journal of Techno-Social, 2017)
This study aims to identify the level of awareness and readiness in using CIDOS E-learning among students in the Department of Electrical Engineering in Politeknik Sultan Salahuddin Abdul Aziz Shah. Aspects of awareness and readiness to use CIDOS were identified for this study. A total of 90 respondents were involved in this study consisting of three programs in the Department of Electrical Engineering, which are Diploma in Electronic Engineering (Medical), Diploma in Electronic Engineering (Control), and Diploma in Electronic Engineering (Communication). The respondents were students of semester two December 2015 Session. Questionnaire method was used in getting relative information. The results were analysed using Statistical Package for Social Sciences (SPSS) version 18. The study found that the level of awareness and readiness of respondents is high with an overall mean of 3.9.